The Mechanism of Budding of Retroviruses from Cell Membranes - Andrew Pincetic; Jonathan Leis (Advances in Virology)
Retroviruses have evolved a mechanism for the release of particles from the cell membrane that appropriates cellular protein complexes, referred to as ESCRT-I, -II, -III, normally involved in the biogenesis of multivesicular bodies. Three different classes of late assembly (L) domains encoded in Gag, with core sequences of PPXY, PTAP, and YPXL, recruit different components of the ESCRT machinery to form a budding complex for virus release. Here, we highlight recent progress in identifying the role of different ESCRT complexes in facilitating budding, ubiquitination, and membrane targeting of avian sarcoma and leukosis virus (ASLV) and human immunodeficiency virus, type 1 (HIV-1). These findings show that retroviruses may adopt parallel budding pathways by recruiting different host factors from common cellular machinery for particle release.